PENGARUH CAPITAL ADEQUACY RATIO, NON PERFORMING LOAN DAN LOAN TO DEPOSITS RATIO TERHADAP PROFITABILITAS BANK NEGARA INDONESIA CABANG SUMBAWA - I Nyoman Sutama (Samalewa: Jurnal Riset & Kajian Manajemen, 2021)
This study aims to determine the effect of the capital adequacy ratio (CAR), non-performing loan (NPL) and loan to deposits ratio (LDR) on the profitability of Bank Negara Indonesia Sumbawa Branch in 2016-2020. The type of data used is quantitative in the form of CAR, NPL and LDR data from the annual financial statements and published income statement published by Bank Negara Indonesia. The data used are time series collected using documentation techniques through the official website of PT. Bank Negara Indonesia. Tbk. and the Indonesia Stock Exchange. Data were analyzed using multiple linear regression analysis techniques and hypothesis testing. The results of this study indicate that the capital adequacy ratio (CAR), non-performing loan (NPL) and loan to deposit ratio (LDR) variables individually have no effect on profitability at Bank Negara Indonesia Sumbawa Branch.